Sodium Glucose Co-Transporter-2 (SGLT 2) Inhibitor as A Therapy For Heart Failure With Low Ejection Fraction (HFrEF) - Muhammad Gilang Dwi Putra; Sidhi Laksono (Universitas Pakuan, 2022)
Heart failure is a major cause of cardiovascular morbidity and mortality worldwide despite advances in prevention and management. Recent clinical trial findings have shown that sodium-glucose co-transporter 2 inhibitor (SGLT2i) produces effects other than lowering blood glucose levels, i.e., exhibits beneficial cardiovascular effects. The purpose of this paper is to determine the role of SGLT2i in heart failure patients with low ejection fraction (HFrEF) so that it can be used as a guide for future management. This study is a narrative review by searching on Google Scholar through several keywords. The period including articles obtained is articles from 2014 to 2022. The diuretic effect of SGLT2i can cause an increase in cardiac preload. The reduction in cardiac afterload likely occurs through a decrease in blood pressure and arterial stiffness resulting in increased endocardial blood flow. SGLT2i has a beneficial effect on the heart remodeling process. SGLT2i can prevent heart failure by increasing the production of ATP from the oxidation of ketone bodiesSGLT2i in heart failure patients can reduce blood pressure, maintain a decrease in eGFR and reduce the risk of acute kidney injury (AKI) in patients. SGLT2i is very effective in the treatment of HFrEF patients. Because of these advantages, further research is needed in Indonesia in order to determine the effectiveness and impact of giving SGLT2i to HFrEF patients in Indonesia.